Exploring future hydrogen development and the impact of policy: A novel investment-led approach - Houghton, Tom; Cruden, A. (Elsevier Science Ltd., 2011)
It is generally recognised that the primary tools being utilised today for hydrogen energy forecasting and policy development take a least-cost approach. While useful for comparing the viability of different technologies from a cost perspective, it is argued that these models fail to capture the potential value contribution such technologies could offer companies and, in consequence, the likelihood of their receiving investment. The authors propose a novel model for forecasting the deployment of hydrogen energy systems based on a company value maximisation approach designed to assist governments in the development of appropriate policy instruments. In this paper a theoretical relationship between market sector valuations and investment activity is presented using 3 value metrics, namely net present value (NPV), earnings per share (EPS) and sum of the parts (SOP). It is shown that, as the electricity and transport fuel markets begin to converge, examination of the effects of different policy measures through the value-led model can highlight otherwise hidden counter incentives. The model further recognises that the propensity to invest in hydrogen differs according to the characteristics of the company looking to make the investment and the implications for policy-makers regarding levels of support are also discussed in the paper.